Open-Cage Fullerene as a Macrocyclic Ligand for Na, Pt, and Rh Metal Complexes - Gao, Rui; Liu, Zhen; Liu, Zeyu; Su, Jie; Gan, Liangbing (Journal of the American Chemical Society, 2023)
An open-cage [60]fullerene derivative was prepared through Malaprade oxidation of a vicinal triol moiety as the key step. Above the 17-membered orifice, there is one carboxyl group. Three ketone carbonyl groups and one lactone carbonyl group are located on the rim of the orifice. The carboxylic and carbonyl oxygen atoms around the orifice act as strong polydentate ligands for a sodium ion. These oxygen atoms also react with [Rh(CO)2Cl]2 to form various isomeric rhodium complexes with comparable stability. The fullerene CC bond on the rim of the orifice forms a stable platinum complex when treated with Pt(PPh3)4. Single crystal X-ray diffraction data reveal that one of the carboxylic oxygen atoms above the orifice forms a H-bond with the water molecule trapped in the cage.